Legal Analysis of Marriage Annulment Due to Identity Forgery in Mixed Marriages (Case Study of Karawang Religious Court Decision Number 3465/Pdt.G/2024/Pa.Krw) - Mulyana, Adin; Amaliya, Lia; Rahmatiar, Yuniar (LEGAL BRIEF, 2025)
The present study examines the legal implications of the dissolution of marriages that have been caused by the fraudulent misrepresentation of identity in the context of mixed marriages, with a particular focus on the analysis of the Court of Religious Affairs in Karawang's decision number 3465/Pdt.G/2024/PA.Krw. The objective of this study is to examine the legal implications and consequences of the dissolution of marriage. The research methodology employed is of a juridical-normative nature, encompassing both an empirical and a theoretical dimension. The present study's findings suggest that marital unions founded upon false identities, as exemplified by the utilization of pseudonyms and the fabrication of citizenship status by one party, do not satisfy the criteria for legality as outlined in Law Number 1 of 1974 concerning Marriage. The dissolution of the marriage in question results in the non-recognition of the marital status and joint assets of the couple. However, the ruling affirmed the legitimacy of the offspring from the aforementioned marriage for the purpose of safeguarding their legal rights. The present study underscores the pivotal role of administrative integrity and transparency in the documentation of mixed marriages, in conjunction with the proactive involvement of state officials in the prevention of any transgressions during the matrimonial process. Data certainly leads to transparency and minimizes the potential for fraud in the 2024 elections.